2003
DOI: 10.1046/j.1464-410x.2003.04054.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality control in urodynamics: a review of urodynamic traces from one centre

Abstract: quality control, e.g. baseline pressures and coughs to test pressure transmission. The data were analysed to establish how often quality criteria were met, and identify areas for improvement. RESULTSIn 100 eligible traces, the baseline detrusor pressure was 0-10 cmH 2 O in 86, and -5 to + 10 cmH 2 O in 94%. Baseline intravesical and abdominal pressure were 30-50 cmH 2 O in 68% and 73% of cases, respectively. Coughs were present before filling in 94%, during filling in 95%, before voiding in 72% and after voidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 15 publications
1
43
2
Order By: Relevance
“…The criteria for assessing an image as high-quality were set by referencing GUP [1] and a retrospective study of urodynamic traces [5]. In addition, we suggest that apart from external pressure changes, such as talking, coughing, moving or Valsalva maneuvers, the P abd during the bladder-filling phase should remain steady.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for assessing an image as high-quality were set by referencing GUP [1] and a retrospective study of urodynamic traces [5]. In addition, we suggest that apart from external pressure changes, such as talking, coughing, moving or Valsalva maneuvers, the P abd during the bladder-filling phase should remain steady.…”
Section: Methodsmentioning
confidence: 99%
“…It has been claimed that intravesical pressure (P ves ) and abdominal pressure (P abd ) traces show the same fine structures and equivalent major changes, while detrusor pressure (P det ) does not change significantly during cough tests. Sullivan et al [5] identified cough signal quality by comparing the measured height of the cough spikes on P abd and P ves tracings, stating that a good cough signal has a smaller spike that is 70%–100% the size of the larger spike. This is a somewhat arbitrary classification of the cough signal.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In clinical practice this lack of reliability can be further compromised by inconsistent practice. 4 Quality control is vital to allow accurate, reproducible, and interpretable pressure readings and to identify artifacts. 5 Since multi-center drug trials assessing the effectiveness and tolerability of drugs often use urodynamic parameters as a primary outcome measure, correct interpretation and communication of findings is essential.…”
Section: Introductionmentioning
confidence: 99%
“…3 Current urodynamic practice, however, varies enormously, with many health care professionals performing urodynamics studies with insufficient training and without good clinical support from senior medical colleagues. 4,5 In the first open meeting to discuss this at the United Kingdom Continence Society (UKCS) annual meeting in 2007 this was a particularly strong theme from nursing colleagues. In a healthcare environment in which there is a growing fear of litigation, several groups have expressed concern about performing urodynamics in a context where they feel unsupported and exposed to risk.…”
Section: Introductionmentioning
confidence: 99%